1999
DOI: 10.1182/blood.v94.4.1440.416k01_1440_1450
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of Big Endothelin-3 by the Kell Blood Group Protein

Abstract: Kell blood group protein shares a consensus sequence (H.E.X.X.H) with a large family of zinc-dependent endopeptidases. Kell has closest homology with neutral endopeptidase 24.11, endothelin converting enzyme-1 (ECE-1), and the PEX gene product that, as a group, comprise the M13 subfamily of mammalian neutral endopeptidases. The proteolytic activity of the M13 members, but not of Kell, has been previously demonstrated. A secreted form of wild-type Kell protein (s-Kell), devoid of the intracellular and transmemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 37 publications
0
53
0
1
Order By: Relevance
“…The Kell protein is an endothelin-3 converting enzyme generating the bioactive endothelin-3. 14,33 Experimental studies demonstrated that endothelin is a neurotrophic factor at low concentrations and a cytotoxic factor at high concentrations, suggesting that endothelinrelated mechanisms might be implicated in neurodegeneration. 34,35 However, no acanthocytosis, cerebral, or neuromuscular signs and symptoms have been described in individuals harboring the K 0 -phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kell protein is an endothelin-3 converting enzyme generating the bioactive endothelin-3. 14,33 Experimental studies demonstrated that endothelin is a neurotrophic factor at low concentrations and a cytotoxic factor at high concentrations, suggesting that endothelinrelated mechanisms might be implicated in neurodegeneration. 34,35 However, no acanthocytosis, cerebral, or neuromuscular signs and symptoms have been described in individuals harboring the K 0 -phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12 Although the precise function of the XK/Kell-complex is not yet clarified, available data suggest an important role in muscle and striatal nerve cell physiology. [12][13][14] The vast majority of disease-causing XK mutations comprise deletions, nonsense mutations, or splicesite mutations predicting absent or truncated XK protein devoid of the Kell protein binding site. 3,4,9,15,16 To date, only two XK missense mutations have been described.…”
mentioning
confidence: 99%
“…31 The Kell blood group antigen is an active enzyme: an endopeptidase that processes endothelin-3, a potent vasoconstrictor, by cleavage of its biologically inactive progenitor. 32 Its function in vivo, however, remains unclear and it is not known whether the Kell glycoprotein processes any other biopeptides. No obvious pathology is associated with the Kell-null phenotype.…”
Section: Contributions Of Blood Groups To Biologymentioning
confidence: 99%
“…1,2 Kell, an endothelin-3-converting enzyme, is a 93-kDa type II membrane glycoprotein that belongs to the M13 family of zinc endopeptidases. 3,4 Like other members of the M13 family, Kell has an intracellular N-terminal domain and a large extracellular C-terminal domain which contains a zinc-binding catalytic pentapeptide consensus sequence, HExxH (in Kell, HELLH). Kell contains five possible N-glycosylation sites and 15 cysteine residues on the ectodomain, predicting a highly folded nature.…”
Section: The Kell and Xk Proteinsmentioning
confidence: 99%